Humans histological evaluation of regenerative activity using Subdermal Induced Heat (S.I.H.) Technology® - Maullu, Giorgio; Pirino, Alessio; Sbarbati, Andrea; Fanelli, Benedetta; Scuderi, Nicolò (Aesthetic Medicine, 2025)
Introduction: The use of radiofrequency (RF) in aesthetic medicine is widely appreciated for its ability to heat cutaneous and muscular tissues, leading to collagen denaturation and stimulating new collagen and elastin production, alongside improved blood flow. However, precise temperature control is essential to avoid surface skin damage. Subdermal Induced Heat (S.I.H.) Technology® represents an advancement in RF application, delivering targeted heat to subcutaneous tissue while preserving skin surface integrity. This technique may improve tissue tone and elasticity, provide analgesic benefits, and accelerate tissue repair. Materials and methods: The study involved five female patients aged 30 to 58, treated with endodermic RF using S.I.H. technology in the abdominal (two cases), gluteal (two cases), and inner thigh (one case) regions. Three patients were treated at 50°C under Klein’s solution, and two at 48°C under local anesthesia, with each session lasting 25 minutes per side. Biopsies were collected pre-treatment (T0), at 1 month (two patients), at 3 months (T1), and at 6 months (T2) post-treatment. Histological analysis was performed using hematoxylin-eosin and orcein staining to assess connective tissue and elastic fibers. Results: Histology revealed significant skin improvements in all patients at six months. Initially, the epidermis was thin, with reduced dermal papillae and deep-seated elastic fibers. At three months, increased vascularization and superficial migration of elastic fibers were noted. By six months, dermal papillae elongation, dermal thickening, and further reorganization and proliferation of elastic fibers were evident, without pathological changes. Discussion: RF is known for its regenerative effects. This study highlights how subcutaneous RF via S.I.H. technology promotes tissue regeneration without inducing elastosis or fibrosis. Significant improvements were observed, especially in younger subjects, including enhanced dermal structure and elastic fiber organization. Conclusions: Endodermic RF using S.I.H. technology stimulates the regeneration of essential skin components safely, ensuring effective results without adverse tissue reactions.